2021
DOI: 10.3389/fvets.2021.758705
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mRNA Expression and Copy Number Variations Within the Goat FecB Gene Associated With Litter Size

Abstract: The Booroola fecundity (FecB) gene, as the first major fecundity gene identified in Booroola sheep, has attracted careful attention. So far, previous research have uncovered the FecB mutation (Q249R) as the main mutation by virtue of which sheep exhibits multiple lambing phenomena. This mutation is now being intensively studied and widely used. However, such effect of the FecB mutation has not been applied to goats, and similar types of the FecB gene in goats still need to be studied. Thus, the current study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In our previous study, five CNVs within Fec B were significantly associated with goat litter sizes [ 16 ]. Given that litter size is positively associated with morphometric traits [ 27 ], association analyses between these CNVs and morphometric traits were conducted in SBWC, GZHM, and Nubian goats.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, five CNVs within Fec B were significantly associated with goat litter sizes [ 16 ]. Given that litter size is positively associated with morphometric traits [ 27 ], association analyses between these CNVs and morphometric traits were conducted in SBWC, GZHM, and Nubian goats.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, differences in breed and sample size may also have contributed to this finding. In our previous study, we identified five CNVs within the Fec B gene in SBWC goats and established that CNV3 and CNV5 were significantly associated with litter size [ 16 ]. Since there is a positive association between litter size and morphometric traits, we hypothesized that the Fec B gene also influences growth performance in goats [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously explored experimental procedures were as follows, 95°C for 45 s, 40 cycles of 15 s at 95°C and 45 s at 60°C. Finally, the result was processed by method 2*2 −Δ Ct ·2*2 −Δ Ct >2 was Gain, it < 2 was Loss, it = 2 was Median genotype ( 29 ).…”
Section: Methodsmentioning
confidence: 99%